Thinking Aloud as an Effective Strategy in Foreign Language Learning: Philosophical Analysis, Methods, and Practical Implementation - Addamegh, Khalid; Al Qahtani, Sara (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2024)
Purpose – This study aims to explore the philosophy, methodology, and practical implementation of the Thinking Aloud strategy in second language (L2) and foreign language learning. Thinking Aloud is a cognitive-based learning strategy that enables learners to verbalize their thought processes, thereby enhancing reflective understanding and active communication skills. Design/methods/approach – This research employs a qualitative approach with a descriptive-analytical design, supported by literature studies from various primary and secondary sources, including Scopus and Springer-indexed journals. Data were analyzed using content analysis based on educational theories, cognitive psychology, and second language studies. Findings – The findings reveal that the Thinking Aloud strategy not only strengthens learners' understanding of the target language but also provides practical insights for educators to identify students' learning challenges. Additionally, this study highlights the potential adaptation of this strategy for cross-cultural learning contexts, which has been underexplored in the literature. Research implications – The primary contributions of this research include the development of a comprehensive guide for Thinking Aloud implementation, the integration of theory and practice, and a holistic approach encompassing philosophical, practical, and critical aspects. Therefore, this study establishes a robust foundation for innovating more reflective and effective language learning methods in the globalization era.الملخصتهدف هذه الدراسة إلى استكشاف فلسفة ومنهجية وتنفيذ استراتيجية